(untitled) (Web of Teachers: Inderscience Research, 2024)
This article is about our great writer Abdullah Qadiri, who laid the foundation for a new genre in Uzbek literature of the twentieth century, the history of his life and work, his works, stories and novels. The article also reflects on the bitter fate of the writer as a result of the repressive policies of the colonial system of that time and the justification of the writer’s personality by independence.